Synthesis of Rice Husk–Based Silica Gel Using Chemical Precipitation Method as an Adsorbent for Cu²⁺ Ions - Anisa Puspita Wardani; Febriana Putri Sagita (Universitas Negeri Semarang, 2025)
Rice husk, an abundant agricultural waste in Indonesia, is a promising source of silica. This study investigates the synthesis of silica gel from rice husks using chemical precipitation and its potential for removing copper ions (Cu²⁺) from wastewater. The silica gel was synthesized by dissolving rice husk ash in a 2 N NaOH solution, followed by precipitation with 1 N HCl. Adsorption experiments were conducted using CuSO₄ solutions at concentrations of 3, 6, and 9 ppm, with varying adsorbent masses (0.3, 0.6, and 0.9 g). The results demonstrated that increasing the adsorbent mass improved Cu²⁺ removal efficiency, with the highest efficiency observed at 0.9 g for the 3 ppm solution, achieving 86.43%. Adsorption isotherms were analyzed using the Langmuir and Freundlich models. The Freundlich model provided a better fit for the data, indicating the heterogeneous nature of the silica gel surface. This study highlights the potential of rice husk-derived silica gel as an effective adsorbent for heavy metal removal, contributing to both waste valorization and environmental protection.